Gender Phenomenon in Short Story by Fanny J. Poyk in Media on Line, Indonesia - Juanda Juanda (Kafa`ah: Journal of Gender Studies, 2018)
This study discuss contemporary feminist genres and innovative techniques PoyK and social issues, traditional and modern culture of women in the short story. Analysis of descriptive  data through library data, relevant research journal articles, online newspapers, short story Fanny J. Poyk "Mince Woman from Notes," Kompas, December 3, 2017; "Belis is Dowry" Kompas January 10, 2016; and "One Day in Metromini" Republika November 12, 2017. Analysis of data on the search for Poyk feminism and social, traditional and modern cultural issues concerning women.The results this research show that the feminist genre in Poyk's imagery in his short story is radical feminism. Feminist movement that rejects parthiarchy. Mince out of the house and earn a living independently. Women have not been sold properly in households and the public sphere. From a cultural point of view there has been a throwback in the culture of marriage in NTT in deciding the wedding dowies 'Belis' have taken place in these modern times. Things that need to be paid attention to economies that demand others can live frugally and practically. Poyk’s short story through characterization reflects the phenomenon of women who have gender inequality in terms of marginalization, subordination, stereotype, violence, and double burden.